Combate ao bullying LGBTQIfóbico na escola: um estudo de caso - Barbosa, Rafael Pires (2022)
This research is a case study that aims to analyze LGBTQIfobic bullying at school and investigate if the event called “Brito sem LGBTfobia”, promoted annually by the State School Professor Joaquim Luiz de Brito, can reduce this type of occurrence on the institution's premises. Its objectives are: (I) to observe and present the pedagogical activities carried out during the event; (II) to know the possible impacts caused in the school community, checking if there are signs of reduction of LGBTQIfobic bullying; and (III) to investigate its influence on the relationships between high school students from their perspective and of the teachers. The research has a qualitative approach and an exploratory character, and its methodological procedures consist of open interviews, consisting of a triggering question, transcription and analysis of its contents. The participants that make up the sample are students and teachers who have already experienced the event and who are available to give an interview related to their experience in this school activity. The framework of this research is based on complex thought and the theoretical categories analyzed are operating principles, imaginary complexes and complex comprehension. The research results show that the subjectivity and imprinting marked by a long socio-historical-cultural process of marginalization of the LGBTQI community represent a strong barrier for "Brito sem LGBTfobia", by itself, to be able to substantially mitigate LGBTQIfobic bullying at school. Even so, the event consists of an important inclusion and self-eco-organization tool for students whose sexual orientation or gender identity is different from cis-heteronormativity.